Purification and characterisation of lectin isolated from Nigeria achatina achatina snail - Odiegwu, C. N. C.; Ukaejiofo, E. O.; Tothill, Ibtisam E.; Chianella, Iva; Okey-Onyesolu, Chinenye F. (GSC Online Press, 2020)
Lectins are carbohydrate-binding proteins that are highly specific for sugar moieties of other molecules. They perform recognition on the cellular and molecular level and play numerous roles in biological recognition phenomena involving cells, carbohydrates, and proteins. Blood groups are inherited characters which give rise to antigen-antibody reaction. A total of 120 samples of local (Nigeria) Achatina achatina snail specie were collected, authenticated at the Zoology Department of the University of Nigeria, Nsukka and 80mls of pooled crude lectin extract was obtained. Purifications were performed on 20mls of the crude extract in three steps viz, Ammonium sulphate precipitation and Dialysis (Partial purifications), Con A Sepharose 4B affinity chromatography column (Complete purification). The affinity purified lectin was used for all the actual tests conducted in this research. The crude, partially and complete/affinity purified lectin extracts were subjected to Haemagglutination tests, Protein Assay and Specific Sugar determinations. The molecular weight was assessed by Sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) method. The results of the research showed as follows: On complete/affinity purification, 15mls of pure sample containing only the high molecular weight lectin was obtained. The respective haemagglutination tests on the crude, partially and affinity purified lectin showed on standardisation, preferential agglutination with Blood group A type. The Protein contents of the lectin was deduced to be as follows: The crude extract contains 13.5mg/dl, Dialysed precipitate – 5.7mg/dl, Dialysed supernatant – 5.0mg/dl and the Affinity purified Lectin – 0.422mg/dl. Galactose N-acetyl amine (Gal NAc) residue was determined to be its specific sugar. The SDS-PAGE analysis showed the molecular weight of the lectin to be 250 KDaltons. This research has therefore succeeded in the Purification, Characterisation and illustration of the lectinic properties of the local Nigeria snail - Achatina achatina
Keywords: Achatina achatina Lectin Purification and Characterisation